2018
DOI: 10.21512/lc.v12i4.4288
|View full text |Cite
|
Sign up to set email alerts
|

Language Attitude and Language Choice in Bilingual Academic Learning Environment

Abstract: The objectives of this research were to observe the language attitude and factors determining language choice of English Department students of Bina Nusantara University. The observation carried out by exploring the motivation, language choice, and language practice of the English Department students. The data were collected through a questionnaire, which was designed to capture the students’ motivation in studying English, language choice, and practice. The result of this research shows that the English depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
(3 reference statements)
0
13
0
Order By: Relevance
“…They need to be fully aware that the use of L1 in their L2 classroom shall be only used to assist in building L2 knowledge, fostering personal interaction among teachers and learners, as well as improving teaching efficacy (Shin, Dixon, & Choi, 2020;Tsagari & Giannikas, 2018). According to Dewi and Setiadi (2018), this will help learners make the right decision as to when to refer back to their L1 at times of L2 linguistic difficult situation in an L2 classroom. These researchers have reported that their participating English majors claim to refer back to the Indonesian language in an English classroom situation where their lecturers decided on using the language because it is much simpler than in English to make a particular complex explanation understandable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They need to be fully aware that the use of L1 in their L2 classroom shall be only used to assist in building L2 knowledge, fostering personal interaction among teachers and learners, as well as improving teaching efficacy (Shin, Dixon, & Choi, 2020;Tsagari & Giannikas, 2018). According to Dewi and Setiadi (2018), this will help learners make the right decision as to when to refer back to their L1 at times of L2 linguistic difficult situation in an L2 classroom. These researchers have reported that their participating English majors claim to refer back to the Indonesian language in an English classroom situation where their lecturers decided on using the language because it is much simpler than in English to make a particular complex explanation understandable.…”
Section: Resultsmentioning
confidence: 99%
“…While several researchers acknowledge that the use of L1 within L2 classroom has a limited role on L2 learning progress (Almohaimeed & Almurshed, 2018;Ghobadi & Ghasemi, 2015;Çelik & Aydın, 2018), others believe that its uses support learners in making the most of their L2 learning. Debreli (2016), for instance, contends that the use of L1 in L2 classroom helps learners, in particular, to understand better teachers' explanation on specific difficult topics and new lexical items, while Dewi and Setiadi (2018), as well as Tsagari and Giannikas (2018), believe that use it in a principled way help teachers and learners to foster L2 teaching and learning. To complement the existing research on this issue by presenting the views of language teachers in an English as a Foreign Language (EFL) classroom setting, the study reported in this research, therefore, seeks to explore teacher educators' (TEs) views on the use of L1 in their L2 classrooms in the context of teacher training institution in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a participant thinks that the use of L1 in teaching English is allowed in teaching English when it is needed (Almoayidi, 2018) to give a comfortable atmosphere to the students (Kocaman & Aslan, 2018). It is because students learn English in the classroom only that they do not have any exposure outside the class (Dewi & Setiadi, 2018).…”
Section: N P R E S Smentioning
confidence: 99%
“…This idea aligns with the notion proposed by Crystal (1998), who defines language attitude as one's psychological construction regarding one's own language or others' language. The attitude intended can be positive or negative (Dewi & Setiadi, 2018;Yürekli & Afacan, 2020). This statement implies that deeds triggering an attitude are related to a motive.…”
Section: Language Attitudes and Language Usementioning
confidence: 99%